Social capital and the cost of equity - Gupta, Atul; Raman, Kartik; Shang, Chenguang (Journal of Banking & Finance, 2018)
We find that a firm's cost of equity is inversely related to the level of social capital in the state where the firm is headquartered. Further, the cost of equity declines when firms move their headquarters from a low-social-capital state to a state with higher social capital. The negative relation between social capital and the cost of equity is statistically significant only for firms facing relatively low levels of product–market competition and is not significant for firms with good firm-specific reputations. We interpret these findings as indicating that social capital serves as a societal monitoring mechanism, and can be value-enhancing for firms that are perceived as having greater agency problems and face weak product market monitoring.